(untitled) - Yacht, Carol (New York, NY, 2013)
In Computer Accounting with Sage 50 Complete Accounting 2013, 17th Edition, you learn about the relationship between Sage 50 software and fundamental accounting principles, procedures, and business processes. The primary goal is for the student to have a working familiarity with the software after completing the course with this text.
Keywords: Accounting,Kế toán; Computer programs,Chương trình máy tính